1995
DOI: 10.1111/j.1467-9280.1995.tb00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Between Picture Naming and Translation: A Test of Asymmetries in Bilingual Memory

Abstract: A transfer paradigm was used to investigate the relationship between picture naming and translation English-Spanish bilniguals first named pictures and subsequently translated words in both their first (LI) and second (L2) languages Some words in the translation task were repetitions of concepts that had previously been named as pictures Whereas picture naming produced reliable transfer to translation from L1 to L2, it produced no transfer to translation from L2 to L1 The results support the claim that connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
124
3
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(147 citation statements)
references
References 20 publications
11
124
3
2
Order By: Relevance
“…The findings of priming from translation to picture naming are consistent with the corresponding effects in our previous research (Francis, 1998;Francis et al, 2002). The finding of priming from picture naming to translation when responding in the nondominant language replicates that of Sholl et al (1995). However, in contrast to the Sholl et al study, substantial priming from picture naming to translation was also observed when responding in the dominant language, which suggests that translation to the dominant language was concept mediated.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The findings of priming from translation to picture naming are consistent with the corresponding effects in our previous research (Francis, 1998;Francis et al, 2002). The finding of priming from picture naming to translation when responding in the nondominant language replicates that of Sholl et al (1995). However, in contrast to the Sholl et al study, substantial priming from picture naming to translation was also observed when responding in the dominant language, which suggests that translation to the dominant language was concept mediated.…”
Section: Discussionsupporting
confidence: 88%
“…(For detailed explanations of the logic behind the use of response time patterns as evidence for concept and word mediation, see Potter et al, 1984;Snodgrass, 1993. ) Arguably the strongest evidence in the literature regarding the concept-mediated or word-mediated nature of translation comes from the Sholl et al (1995) study of repetition priming in late English-Spanish bilinguals living in a primarily English-speaking environment. Picture naming in the nondominant language primed translation to the nondominant language, indicating that translation to the nondominant language was concept mediated.…”
Section: Implications For Bilingual Language Processingmentioning
confidence: 99%
“…In line with predictions of RHM, translation asymmetry effect has been found in many earlier cross-language studies using different tasks and stimulus material (e.g., Kroll & Curley, 1988;Kroll & Stewart, 1994;Kroll & Sholl, 1992;Sholl, Sankaranarayanan, & Kroll, 1995).…”
Section: Introduction and Methodssupporting
confidence: 61%
“…Participants were screened for proficiency with a picture naming/translation task (Snodgrass & Vanderwart, 1980, normed for L2 by Sholl, Sankaranarayanan & Kroll, 1995) and a sentence grammaticality judgment task (Johnson & Newport, 1989). In the picture-naming task, participants saw 80 pictures on the computer screen and gave the English name for what appeared in the line drawing.…”
Section: Methodsmentioning
confidence: 99%